2016
DOI: 10.2139/ssrn.2964208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ISO 9001 on Non-Financial and Financial Performance in the Organizations: A Review

Abstract: ABSTRACT:The main purpose of this paper was to specify the impact of ISO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Unfortunately, regardless of all these researches clarifying the reason why full benefit of ISO certification is not attained, effect of QMS on performance remains controversial with a number of empirical studies alluding to nullity of ISO certification on performance (Nyakio Kibe & Wanjau, 2014). Empirical studies showed that the effect of ISO 9001 standard or organization's performance is inconsistent and unclear (Neyestani, 2017). Although improving production process has consistently attained positive result, customers' results and financial performance were inconclusive and unclear because organizations with different quality management context have significantly different performance outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, regardless of all these researches clarifying the reason why full benefit of ISO certification is not attained, effect of QMS on performance remains controversial with a number of empirical studies alluding to nullity of ISO certification on performance (Nyakio Kibe & Wanjau, 2014). Empirical studies showed that the effect of ISO 9001 standard or organization's performance is inconsistent and unclear (Neyestani, 2017). Although improving production process has consistently attained positive result, customers' results and financial performance were inconclusive and unclear because organizations with different quality management context have significantly different performance outcomes.…”
Section: Introductionmentioning
confidence: 99%